LINGKUNGAN PENDIDIKAN DAN MOTIVASI BELAJAR DI ERA GLOBALISASI - Rohimat Nurhasan; Syamsu Yusuf LN (Journal Civics and Social Studies, 2020)
AbstractThis article presents an attempt to model the interrelationship between student motivation in an educational environment that utilizes several indicators of empirical evaluation. This study uses an empirical study research design. An in-depth study of qualitative research results is used to develop an understanding of the educational environment in relation to student motivation. Learn about the relationship between the educational environment with student motivation. The role of parents, sensitivity, communication and increased learning motivation.